Security council reform proposals : a comparative analysis - Khairul, Syahrir (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
The purpose of this study is to compare four Security Council reform proposals: the Razali Plan, the Group of Four, the Uniting for Consensus, and the African Union's proposal. This descriptive and qualitative study is based on data obtained from the United Nations' documents, academic journals, books, theses, magazines and newspapers. The proposals are analyzed using three values stated in the United Nations Millennium Declaration: freedom, equality, and shared responsibility. These and other reform proposals were the results of globalization, the democratic waves, and the emergence of new powers. The four proposals have many similarities. However, the Razali Plan came closest to the United Nations Millennium Declaration values. Nevertheless, the four proposals failed as each of them promoted its each own agenda and was opposed by power blocs in the United Nations system. The factors that generated momentum for reforms continue to operate and will exert pressure to reform the United Nations Security Council.